Genotype III-Based Japanese Encephalitis Vaccines Exhibit Diminished Neutralizing Response to Reemerging Genotype V - Lee, Ah-Ra; Kim, Woo-Jin; Choi, Haeyoun; Kim, Sang-Hyun; Hong, Su-Yeon; Shim, Sang-Mu; Lee, Hee Il; Song, Jae Min; Kim, Seong-Jun; Ishikawa, Tomohiro; Kang, Ji-Man; Eom, Hyeon-Seok; et al. (The Journal of infectious diseases, 2025)
Japanese encephalitis (JE) has been predominantly controlled through vaccination. However, the isolation of JE virus (JEV) genotype V (GV) in China in 2009, and the subsequent alarming increase in JE cases in the Republic of Korea since 2010, present a new challenge. Serum samples from individuals vaccinated with genotype III (GIII)-based JE vaccines were analyzed for neutralizing seroresponse to GV isolates. Serum from immunocompromised pediatric patients vaccinated with an inactivated JE vaccine showed higher 50% plaque reduction neutralization test geometric mean titer (GMT) against GIII Nakayama (11 358; 95% confidence interval [CI], 1790-29 658), but lower GMTs against GV isolates: GV Muar (499; 95% CI, 0-2437), GV 43279 (308; 95% CI, 159-582), and GV 43413 (231; 95% CI, 108-738). Similarly, 32 healthy volunteers receiving a live attenuated JE vaccine achieved 100% seroprotection against GIII Nakayama with GMT of 338 (95% CI, 304-651) at 1 month postvaccination. However, GMTs against GV isolates were 123 (95% CI, 102-446) for GV Muar, 81 (95% CI, 63-168) for GV 43279, and 107 (95% CI, 100-322) for GV 43413, not achieving 100% seroprotection against these isolates. At 6 months postvaccination, GMT against Nakayama increased to 696 (95% CI, 409-2353), while remaining similar for GV isolates. Our study underscores that current GIII-based vaccines do not provide comparable protection against GV JEVs, impacting individuals in both current and potential endemic regions, as well as travelers to these regions.